Emergency medicine physician burnout and wellness in Canada before COVID19: A national survey. Issue 5 (September 2020) - Lim, Rodrick; Aarsen, Kristine Van; Gray, Sara; Rang, Louise; Fitzpatrick, Jada; Fischer, Lisa
ABSTRACT: Introduction: Emergency medicine (EM) is a high-risk specialty for burnout. COVID-19 has had and will continue to have important consequences on wellness and burnout for EM physicians in Canada. Baseline data are crucial to monitor the health of EM physicians in Canada, and evaluate any interventions designed to help during and after COVID-19. Objectives: To describe the rates of burnout, depression, and suicidality in practicing EM physicians in Canada, just before the COVID-19 pandemic. Methods: A modified snowball method was used for survey distribution. Participants completed the Maslach Burnout Inventory – Health Services Tool (MBI-HSS), a screening measure for depression (PHQ-9), and a question regarding if the physician had ever or in the past 12 months contemplated suicide. Results: A total of 384 respondent surveys were included in the final analysis: 86.1% (329/382) met at least one of the criteria for burnout, 58% (217/374) scored minimal to none on the PHQ-9 screening tool for depression, 14.3% (53/371) had contemplated suicide during their staff career in EM, and of those, 5.9% (22/371) had actively considered suicide in the past year. Conclusion: Canadian EM physicians just before the COVID-19 pandemic had an alarming number of respondents meet the threshold for burnout, confirming EM as a high-risk specialty. This important baseline information can be used to monitor the physical and mental risks to EM physicians during and after COVID-19, and evaluate support for mental health and wellness, which is urgently needed now and post pandemic.